2008
DOI: 10.1002/cncr.23469
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging of neuroendocrine tumors with combined PET/CT using 68Ga‐DOTATATE (DOTA‐DPhe1,Tyr3‐octreotate) and 18F‐FDG

Abstract: BACKGROUND. The aim was to assess the relevant distribution of the novel PET tracer 68Ga‐DOTATATE in neuroendocrine tumors (NETs) with combined positron emission tomography / computed tomography (PET/CT) and compare its performance with that of 18F‐FDG PET/CT. METHODS. The imaging findings with 68Ga‐DOTATATE and 18F‐FDG on 38 consecutive patients with a diagnosis of primary or recurrent NET were compared and correlated with tumor grade on histology based on ki67 and mitotic index. RESULTS. The sensitivity of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
355
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 432 publications
(373 citation statements)
references
References 20 publications
7
355
3
8
Order By: Relevance
“…There was no significant difference between the 2 tracers in the tumor detection rate of G2 and G3 tumors. Within the literature, there is evidence that somatostatin receptor PET is of limited value in patients with G3 NETs and that 18 F-FDG PET may be more suitable in these cases (18). In our study, however, 68 Ga-DOTATATE and 68 Ga-DOTANOC PET detected significantly more G3 lesions (82% and 90%, respectively) than did 18 F-FDG PET (58%).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…There was no significant difference between the 2 tracers in the tumor detection rate of G2 and G3 tumors. Within the literature, there is evidence that somatostatin receptor PET is of limited value in patients with G3 NETs and that 18 F-FDG PET may be more suitable in these cases (18). In our study, however, 68 Ga-DOTATATE and 68 Ga-DOTANOC PET detected significantly more G3 lesions (82% and 90%, respectively) than did 18 F-FDG PET (58%).…”
Section: Discussioncontrasting
confidence: 78%
“…Somatostatin receptor PET has shown promising results in NETs, with a higher lesion detection rate than is achieved with 18 F-fluorodihydroxyphenyl-L-alanine PET, somatostatin receptor SPECT, CT, or MR imaging (10,11,22,23). Currently, 68 Ga-DOTATOC, 68 Ga-DOTATATE, and 68 Ga-DOTANOC are the most established somatostatin receptor PET tracers (13 68 Ga-DOTATATE and 68 Ga-DOTANOC) showed a similar diagnostic accuracy for these tracers for the detection of NETs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have seen the development of other radiopharmaceuticals suitable for detecting NETs [14][15][16], but under certain circumstances, F-18-FDG PET can also be of diagnostic importance in NET patients with high proliferation index [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kayani et al 14 of 68 Ga-Dotatate and 18 F-FDG PET/CT in 38 NET patients found a higher sensitivity (88%) for 68 Ga-Dotatate, particularly in welldifferentiated tumours, compared with 18 F-FDG PET/CT (66%). Other PET radiopharmaceuticals were also found to be inferior to 68 Ga-peptides.…”
Section: Pet/ct With Gallium-68 Peptidesmentioning
confidence: 97%